PHB3 interacts with BRI1 and BAK1 to mediate brassinosteroid signal transduction in Arabidopsis and tomato - Li, Cheng (The New phytologist, 2024)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.